The Influence of Work Stress on Employee Work Motivation in Regional Assets and Financial Agency in Barru District - Afriansyah; Dipoatmodjo, Tenri S.P.; Ruma, Zainal; Sahabuddin, Romansyah; Burhanuddin; Syahrul, Khaidir (Economics and Business Journal (ECBIS), 2023)
This research examines The Influence of Work Stress on Employee Work Motivation in Financial Institutions and Regional Assets of Barru Regency. The purpose of this research is to find out The Influence of Work Stress on Employee Work Motivation in Financial Institutions and Regional Assets of Barru Regency. This research approach is quantitative. This research was conducted at the Regional Financial and Asset Agency of Barru Regency. The sample used was 68 people. Data collection techniques in the form of observation, questionnaires and documentation. Data analysis techniques include validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, t test (partial) and coefficient determination test (r2). The research results show thatwork stress has a negative and effect onwork motivation. The higher the work stress experienced by employees, the morework motivationemployees are decreasing. When an employee in carrying out his duties, gets a high work load, will take actions that can reduce the quality of his work there by reducing motivation at work. So it is concluded thatwork stress havenegative influenceto work motivation at the Regional Financial and Asset Agency of Barru Regency.